KARAKTERISTIK PENGELOLAAN SAMPAH RUMAH TANGGA SKALA KOMUNITAS DI KOTA SEMARANG - Jawoto Sih Setyono; Nafisah Anas; Erma Maulana Putri; Samsul Ma’rif (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2018)
As population growth increases due to rapid urbanization in the City of Semarang, domestic solid waste generated by households is also increasing. As a consequence, Semarang City is required to be able to manage domestic and non-domestic waste systems more effectively. Technically, domestic waste management in the city of Semarang is carried out by taking and storing garbage in a garbage collection site (TPS) and transfering it into the Jatibarang landfill for final processing. While there is only one system at city level, solid waste management at community level has various forms. The variety of solid waste management at community scale has potentially led to unsustainable outcome because the knowledge and ability of the community to manage waste varies among subdistricts in the city. This study aims to identify variations and characteristics of solid waste management at community scale in the city of Semarang. The research applied quantitative method with descriptive statistical analysis techniques as the main analytical tool. This research was conducted at the household scale as part of the community. The study was carried out in three geographically different locations that represent the distinctive characteristic of Semarang City. The results showed that there were four general forms of solid waste management, namely individual-city management, individual-recycling-city management, communal-city management, and pure individual management. The findings of this study can be used for further research related to the development of solid waste management models at the community scale in Semarang City.